Coenzyme Q10 supplementation in adult-onset focal segmental glomerulosclerosis caused by the Chinese common pathogenic variant c.737G > A (p.Ser246Asn) in the COQ8B gene - Shi Jin; Yiqin Shi; Pan Lin; Hong Liu; Xialian Xu; Xuantong Dai; Gengru Jiang; Xiaoqiang Ding; Fujun Lin (Renal Failure)
COQ8B nephropathy, a mitochondrial disorder caused by mutations in the COQ8B gene, is a major pediatric genetic focal segmental glomerulosclerosis (GFSGS) etiology and stands out as one of the few treatable forms with good response to coenzyme Q10 (CoQ10) supplementation. As the diagnosis and clinical experience of COQ8B nephropathy were predominantly in the pediatric population, the long-term efficacy of CoQ10 supplementation and its application in the adult-onset patients remains largely unknown. Here, we report three cases of adult-onset FSGS from unrelated families, all carrying the Chinese common COQ8B mutation (c.737G > A; p.Ser246Asn) with divergent trajectories of renal function following CoQ10 supplementation initiated in different stages of renal dysfunction, providing valuable evidence on the implication of early disease diagnosis and prompt CoQ10 supplementation for the prognosis of adult patients affected with COQ8B nephropathy.